Coping with Transitions: A Study of International Undergraduate Students at a Private Institution - Shariffah Bahyah, Syed Ahmad (2021)
The intensity of the transition experience faced by international students is attributed to the multiple fronts of challenges faced including the change of academic systems, sociocultural adjustments and limited access to familiar support due to distance and situation. This research was an in-depth study of the experiences of international students at a Malaysian private tertiary institution during the transition period of moving in, moving through and moving out of a university environment. It explored their lived experiences, ascertained their challenges and identified the resources, in the form of assets and liabilities, and other factors that influenced these experiences. Due to the exploratory nature of the objective, the phenomenological design was adopted not just to explore but to interpret their lived experiences. Data was gathered via semi-structured interviews with 19 undergraduate students who were at different stages of the transition experience. The Theory of Transition by Nancy Schlossberg, which espouses studying how individuals approach a transition in terms of the impact and the changes the transition brings to their life, was used as the theoretical framework. This study reveals a dynamic journey of continual growth and progress which unfolded throughout the transition experience. To a certain extent, this growth was made possible due to a balance of experiences consisting of difficult challenges at one end of the spectrum and enjoyable memorable moments at the other. Other factors that made growth possible were the assets and liabilities in their possession, identified based on Schlossberg’s 4 S System: Situation, Self, Support and Strategies. These factors did not act in isolation; they interacted in various combinations. Of particular novelty among the findings is the streamlining of challenges into categories of Psychosocial, Administrative, Physical and Academic (PAPA). The findings led to the identification of systems that work and those that need work. Although this study focussed on the students of one institution, some of their experiences were influenced by government policies that were applicable to all private tertiary institutions. When it comes to institution-specific elements, the systems that work are essentially ‘best practices’. For the systems that need work, further discussions need to be held since many of these originate from policy-level decisions that affect the transition experience of international students in Malaysia.